Efektifitas Zakat Produktif dalam Pemberdayaan Ekonomi Mustahik: Studi Pendahuluan Pada Badan Amil Zakat (BAZ) Kabupaten Gresik - Savid, Ahmad Nashiruddin (Falah: Jurnal Ekonomi Syariah, 2017)
The discourse of poverty is an interesting topic as well as an enduring problem that never resolved. Various ways are done to overcome poverty, one such effort is the optimization of the management of zakah, infaq and alms (ZIS). Amil Zakah Agency of Gresik Regency has distributed zakat productively as a grant of venture capital so that zakah can be developed. The measurement of zakah funds need to be done to determine the level of effectiveness of achievement of productive utilization of zakah. Technique of collecting data in this research is done by interview, observation and documentation. The sample is determined purposively likewise the chairman or head of the BAZ of Gresik Regency, the utilization division or the distribution of BAZ of Gresik regency, the staff and the mustahik of the beneficiaries of the utilization of productive zakah. The research finding shows that the concept of utilization of productive zakah on the mustahik’s economic empowerment undertaken by BAZ Gresik Regency poured into several programs which formed to three types of productive utilization of zakah, namely: (1) empowerment of livestock rolling either individual or collective, (2) empowerment of revolving capital, (3) Provision of work tools. The indicator of effectiveness in this research using Ni Wayan Budiani’s theory of effectiveness with four indicators of program, namely: the accuracy of program targets, program socialization, program objectives and program monitoring. The results of this study indicate that the indicators of accuracy of program targets and program monitoring have been effective, while two others have not been effective.